Disaster governance and the scalar politics of incomplete decentralization: Fragmented and contested responses to the 2011 floods in Central Thailand - Marks D. (2017)
© 2015 Elsevier Ltd. This paper applies the politics of scale as a framework to examine how decentralization reforms and the associated power relations between government agencies at different levels affected disaster risk outcomes in Thailand, particularly during the 2011 floods in Central Thailand. It argues that Thailand's decentralization has been incomplete due to the retention of power and resources by central bureaucrats and the continued weak capacity of local administrative organizations (LAOs). In addition, the country's overall fragmented and politically polarized governance has hindered policy coherence at all levels, including the local level. Incomplete decentralization alongside persistent fragmentation along ministerial and sectoral lines has undermined disaster governance and distributed risks unevenly and unfairly. The governance weaknesses visibly materialized during the 2011 floods. Except for the Bangkok Metropolitan Administration (BMA), LAOs once again had insufficient capacity to effectively respond to the floods and were given insufficient assistance by the central government. The central government sought to monopolize power, did not consult local communities, had limited capacity to enforce all of its decision, distributed risks unevenly, and overall performed poorly. Similarly, the BMA dominated other much smaller local government units within and beyond its formal boundaries.